1991
DOI: 10.1007/bf00260718
|View full text |Cite
|
Sign up to set email alerts
|

Preprosubtilisin Carlsberg processing and secretion is blocked after deletion of amino acids 97-101 in the mature part of the enzyme

Abstract: Summary. During an investigation into the substrate specificity and processing of subtilisin Carlsberg from Bacillus licheniformis, two major independent findings were made: (i) as has been shown previously, a stretch of five amino acids (residues 97-101 of the mature enzyme) that loops out into the binding cleft is involved in substrate binding by subtilisin Carlsberg. In order to see whether this loop element also determines substrate specificity, the coding region for these five amino acids was deleted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Similar results were obtained in studies on another subtilisin derivative in which four residues had been deleted from the substrate-binding cleft (494). Thus, in this exceptional case, cleavage of the propeptide rather than the signal sequence seems to be required for release from the cytoplasmic membrane.…”
Section: Monotopic Membrane Proteinssupporting
confidence: 78%
“…Similar results were obtained in studies on another subtilisin derivative in which four residues had been deleted from the substrate-binding cleft (494). Thus, in this exceptional case, cleavage of the propeptide rather than the signal sequence seems to be required for release from the cytoplasmic membrane.…”
Section: Monotopic Membrane Proteinssupporting
confidence: 78%
“…We propose that substrate specificity may not only be modulated by natural variations in the amino acid sequence of segment 96-104, but also by variations in the length of this exposed loop (VR7). Indeed, deletion of residues 97 -101 in BLSCAR abolishes activity (Schülein et al, 1991) and our own engineering studies of LLSK11 have demonstrated that deletions, insertions and point mutations in this loop can alter specificity and catalytic activity (P.Vos, I.van Alan-Boerrigter, P.Bruinenberg, F.A. Exterkate, M.Nijhuis, W.M.de Vos and R.J.Siezen, in preparation) .…”
Section: Discussionmentioning
confidence: 99%